Research on the Application of Dynamic Programming Algorithm for Load Balancing on Conveyor Lines in the Pharmaceutical Industry - Klymenko, O. (My University, 2024)
The use of robotic sorters in the pharmaceutical industry requires the development of effective balancing algorithms that can take into account the variety of products, their characteristics and processing speed requirements . Research in this area will allow to develop optimal load management strategies, increasing production efficiency and minimizing the errors probability. The use of balancing algorithms in the pharmaceutical industry also helps to reduce costs, optimize production times and ensure compliance with quality standards. Due to the constant changes in market demands and technological developments, research in this area provides an opportunity for continuous improvement and optimization of production processes in the pharmaceutical field.
Keywords: pharmaceutical industry; robotic sorters; balancing algorithms